Improving Science Learning Outcomes through a 5M Based Scientific Approach for Class IV Students at Madrasah Ibtidaiyah Imam Syafi'i Gorontalo - Kulati, Sri Jian; Isa, Abd Hamid; Mooduto, Yulanti S (Newinera Publisher, 2024)
This research aims to improve science lesrning outcomes trhough a scientific approach by applying the 5Ms, namely (Observe, Ask, Try, Reason and Communivate). The approach used show that 5m based learning has been implementated in science learning using a scientifi approach with the activities of observing, acking, trying, reasoning and comunacating.